2022
DOI: 10.1002/cmtd.202100098
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Flow Synthesis of NHC‐Coinage Metal Amido and Thiolato Complexes: A Mechanism‐based Process Development

Abstract: The first continuous flow syntheses of amido and thiolato families are reported. Our studies focused on [M(NHC)(Cbz)] (Cbz=carbazolyl) and [M(NHC)(SPh)] (NHC=N‐heterocyclic carbene) as general proof‐of‐concepts and has led to a simple protocol with unprecedented short reaction times and high product yields. The scope of supporting ligands and substrates permits to assess the versatility of the process and a one‐pot synthesis starting from the imidazolium salt, metal source and carbazole substrate highlights th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…(Scheme 1) We recently reported the synthesis of compound 1 b using a flow reaction setup in just two minutes of residence time as a proof of concept dealing with carbolinederived CMAs. [34] We showed that the limitations of the original batch protocol, regarding prolonged reaction times when sterically demanding ligands were used, [23a] could be overcome by using flow technology. Therefore, the fact that a CMA derived from the sterically demanding harmine can be accessed under the standard conditions without requiring an exceedingly long reaction time is notable.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…(Scheme 1) We recently reported the synthesis of compound 1 b using a flow reaction setup in just two minutes of residence time as a proof of concept dealing with carbolinederived CMAs. [34] We showed that the limitations of the original batch protocol, regarding prolonged reaction times when sterically demanding ligands were used, [23a] could be overcome by using flow technology. Therefore, the fact that a CMA derived from the sterically demanding harmine can be accessed under the standard conditions without requiring an exceedingly long reaction time is notable.…”
Section: Resultsmentioning
confidence: 99%
“…Their complexes with Transition Metals have recently attracted ample attention for their applications in medicinal chemistry [41] . Although complexes with coinage metals have been reported, [41] CMAs of this type are not known, aside from one compound synthesized in our report as a proof of concept [34] . Herein, we report the sustainable synthesis of a range of carboline‐derived CMAs and we evaluate their antiproliferative properties on cell lines and organoids.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations